Development of a flipped classroom-based e-module to improve problem-solving abilities and learning independence of high school students - Avi Dwi Ayunda; Himmatul Hasanah; Nur Aeni Ariyanti (University of Muhammadiyah Malang, 2024)
Non-optimal use of teaching materials and learning techniques impacts students' low skills, especially problem-solving abilities and learning independence. The study aims to develop a flipped classroom-based e-module that is feasible, practical, and effective in improving students' problem-solving skills and learning independence. This research and development use the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Next, the field trial design uses a quasi-experimental method with a non-equivalent control group design, which means using two groups, namely experimental and control. The research subjects were students from SMA N 1 Seyegan who were selected using a cluster random sampling technique with a lottery system. Through drawing, class XI MIPA 3 was obtained as the control class and XI MIPA 4 as the experimental class, each consisting of 34 students. The data collection instruments used were product assessment questionnaires from material experts, media experts, biology teachers, and students, as well as independence questionnaires and problem-solving ability test instruments. Hypothesis testing was carried out using multivariate testing. The research results show that the e-module is considered suitable for use in learning based on material and media experts, is considered practical in its use according to the assessment of teachers and students, and is effective in improving problem-solving abilities and learning independence.